HUBUNGAN KESEHATAN MENTAL DENGAN KEMAMPUAN MENGELOLA STRES AKADEMIK MAHASISWA PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS MUHAMMADIYAH METRO - azizah1 nura; Iswati (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
This study was motivated by the high level of academic pressure experienced by students, which has the potential to affect their mental health, particularly among students in the Islamic Religious Education program who also face moral and spiritual demands. Meanwhile, empirical data regarding the relationship between mental health and the ability to manage academic stress remains limited. This study aims to analyze the relationship between mental health and the ability to manage academic stress among students in the Islamic Religious Education program at Muhammadiyah Metro University. The study employed a descriptive quantitative approach using a correlational method, involving 67 respondents selected via proportionate stratified random sampling from a population of 500 fifth- and seventh-semester students. Data were collected using a Likert-scale questionnaire that had been validated for validity and reliability, and analyzed using tests for normality, linearity, and Pearson’s Product-Moment correlation. The results of the study indicate a positive and significant relationship between mental health and the ability to manage academic stress, with a correlation coefficient of r = 0.712 and a significance level of 0.000 < 0.05, indicating a strong relationship. It is concluded that the better the students’ mental health, the higher their ability to manage academic stress adaptively.